Performance of Proton Green Mobility Challenge electric car - M. Surenderen, Morgan (2013)
This project report deals with performance of electric vehicle Proton Green Mobility Challenge (PGMC) 2012 which won first place in best acceleration and make UMP proud of it. The performance of this proton saga converted to electric needs to be evaluated. The performance test is done on chassis dynamometer which is in the lab at University Malaysia Pahang (UMP). The objective of this project is to determine the performance of electric car with respect to power, torque and voltage drop of the battery while using it. The method that was conducted during the performance test is two tests which are performance curve test and acceleration test. Both tests are done into two modes which is economy and power mode. From result, the economy mode is a power saving mode which produce low power, low torque and low voltage consumption meanwhile the power mode is for high performance mode. In power mode, the car produces high torque, power and consumes a lot of voltage. The performance is done for first, second and third gear. As a conclusion the performance of first gear economy mode has reach maximum power is 21.82 kW and maximum torque of 103 Nm. The performance for the second gear economy mode has reached maximum power of 22.89 kW and the maximum torque is 56 Nm. The performance of third gear economy mode has reached maximum power of 24.71 kW and maximum torque is 30 Nm. The performance of first gear power mode has reach maximum power is 37.8 kW and maximum torque of 198 Nm. The performance for the second gear economy mode has reached maximum power of 40.1 kW and the maximum torque is 130 Nm. The performance of third gear economy mode has reached maximum power of 40.5 kW and maximum torque is 51 Nm. The main criterion that changes the mode of the car is the need for the torque and power. In the acceleration test, economy mode reaches a distance of quarter mile in 31.8 second while in power mode, it took 28 seconds.